Acute effects of stretching routines with and without rest intervals between sets in the bounce drop jump performance - Marchetti, P. H.; Soares, E. G.; Silva, F. H. D. O.; Nardi, P. S. D. M.; Serpa, É. P.; Gomes, W. A.; Schoenfeld, B. J. (International Journal of Sports Science, 2015)
The purpose of this study was to evaluate the acute effects of static-stretching (SS) session with (intermittent) and without (continuous) rest intervals between sets on the bounce drop jump performance, with the same volume and intensity. The experimental protocol consisted of (1) a brief warm-up using sub-maximal jumps; (2) a pre-SS evaluation (passive ankle ROM and three trials of maximal single-leg jumping task for each lower limb); (3) ankle plantar flexors SS protocol (intermittent or continuous) was used only for a single-lower limb; (4) immediate post-SS evaluation (passive ankle ROM and three trials of maximal single-leg jumping task for the stretched lower limb). Then, subjects rest for 30 minutes and the topics 3-4 were repeated with the other lower limb and stretching protocol. The intensity used for both stretching protocols was between 70-90% of the point of discomfort. There were significant decrease in jumping height performance for both stretching protocols: continuous (P=0.001) and intermittent (P=0.006). There were significant increase in contact time only for the continuous protocol (P=0.025). Our findings indicated that both stretching protocols (intermittent or continuous) were effective to increase the passive ankle ROM, and to decrease the single-leg jump height, however only the continuous SS protocol showed increases in the contact time.